1977
DOI: 10.4315/0362-028x-40.5.296
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Polychlorinated Biphenyls (Aroclor 1254) in Lactating Bovines and Their Distribution in Dairy Products

Abstract: Lactating cows were given orally, single or multiple graded doses of polychlorinated biphenyls (PCB) as Aroclor 1254 and the tissue distribution and excretion were measured. Persistence of PCB in milk was determined at all dose levels of PCB administered. A distinct predilection of PCB for tissues with high lipid content was noted. Similarly, PCB appeared in higher concentration in dairy products with high fat content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This conclusion is supported by the literature. In several studies, the concentrations of various PCDD/F and PCB have been found to be at least an order of magnitude higher in fat than in other tissues (11)(12)(13).…”
Section: Model Structurementioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is supported by the literature. In several studies, the concentrations of various PCDD/F and PCB have been found to be at least an order of magnitude higher in fat than in other tissues (11)(12)(13).…”
Section: Model Structurementioning
confidence: 99%
“…It is therefore reasonable to assume that the hydrophobic compounds in the blood are in equilibrium with those in the milk glands. In those feeding studies with hydrophobic compounds where the blood and milk concentrations were both measured, the time courses were very similar (11,13), and where the concentrations were determined on a fat basis, they were virtually the same in blood and milk (25).…”
Section: Model Structurementioning
confidence: 99%
“…gelatine capsule) into the rumen. The time of exposure in feeding studies varied from 1 d (62,75,79,80,87,88,95,97,98,102,103,120,(124)(125)(126) to several weeks (<28 d) (60,77,78,98,113) (Table 2). In some feeding studies, the animals were exposed to PCDD/Fs and PCBs during their dry period (61,88,91,93,94,100,114,115,119) .…”
Section: Exposure Scenarios In Dairy Cattlementioning
confidence: 99%
“…limit of quantification). Dairy cattle Dairy (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82) Holstein cows Dairy (41,83,84) Holstein Friesian Dairy (85) English Holstein Friesian Dairy (86) Italian Holstein Friesian Dairy (87)(88)(89)(90)(91)(92)(93)(94) German Holstein Dairy (95)(96)(97)(98) Jersey Dairy (99,100) Angler Dairy German Red Pied German Black Pied (61,(101)(102)(103)(104)(105) Fries Holland Dairy (106,107) Guernsey Dairy (108) Brown Swiss Dairy (109)(110)(111)(112)(113)(114) Simmental Dual purpose (43,115) Simmental cr...…”
Section: Exposure Scenarios In Dairy Cattlementioning
confidence: 99%
See 1 more Smart Citation